Implementasi Penerapan Restorative Justice terhadap Pelaku Tindak Pidana Narkotika Berdasarkan UU RI No. 20 Tahun 2025 tentang KUHAP - Yudi Tri Yono; Aturkian Laia (INDO PUBLISHING, 2026)
The enactment of Law No. 20/2025 concerning the New Criminal Procedure Code integrates restorative justice into national law. This normative legal research aims to analyze the implementation of restorative justice for narcotics offenders and identify its operational challenges. The findings indicate that the New Code provides clear legal demarcation; closing the gap for dealers while opening a rehabilitation-based diversion scheme for pure users through mandatory Integrated Assessment Team (TAT) recommendations. This integration provides strong legal certainty to restore victims and reduce prison overcrowding. However, its field effectiveness remains hindered by limited government rehabilitation facilities, disparities in law enforcers' understanding, and social stigma. Multi-sectoral formal synergy must be strengthened through implementing Government Regulations to optimize substantive justice.